2008
DOI: 10.1128/mcb.02074-07
|View full text |Cite
|
Sign up to set email alerts
|

A Member of the p38 Mitogen-Activated Protein Kinase Family Is Responsible for Transcriptional Induction ofDopa decarboxylasein the Epidermis ofDrosophila melanogasterduring the Innate Immune Response

Abstract: Rather, Ddc transcription depends on a previously uncharacterized member of the p38 mitogen-activated protein kinase family, p38c. We propose that the involvement of DDC in a new pathway involved in Drosophila immunity increases the levels of dopamine, which is metabolized to produce reactive quinones that exert an antimicrobial effect on invading bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 90 publications
3
49
0
Order By: Relevance
“…Some of these differences could be explained by functional differences of Laz in the Ddc cuticular domain of expression. Since epidermal DA production is triggered in stress situations (Neckameyer and Weinstein, 2005;Sekine et al, 2011) and Ddc functions downstream of the stressresponsive JNK signaling cascade upon a septic cuticle injury (Davis et al, 2008), a contribution to epidermal Laz expression might not be negligible under the stress situations used in our experiments. DA production is particularly important in females, where it controls the last biochemical steps toward the production of female-specific long-chain hydrocarbons with pheromonal functions (Wicker-Thomas and Hamann, 2008).…”
Section: Lazarillo Protects Flies Against Different Forms Of Stress Imentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these differences could be explained by functional differences of Laz in the Ddc cuticular domain of expression. Since epidermal DA production is triggered in stress situations (Neckameyer and Weinstein, 2005;Sekine et al, 2011) and Ddc functions downstream of the stressresponsive JNK signaling cascade upon a septic cuticle injury (Davis et al, 2008), a contribution to epidermal Laz expression might not be negligible under the stress situations used in our experiments. DA production is particularly important in females, where it controls the last biochemical steps toward the production of female-specific long-chain hydrocarbons with pheromonal functions (Wicker-Thomas and Hamann, 2008).…”
Section: Lazarillo Protects Flies Against Different Forms Of Stress Imentioning
confidence: 99%
“…In addition, Ddc expression can be induced in the larval and adult epidermis upon local infection, as part of the immune response (Davis et al, 2008). Ddc basal expression in adult epidermis is small compared to the expression in the CNS domain (Davis et al, 2008). In view of these data the large extension of lifespan caused by Laz expressed under the control of the Ddc driver (Fig.…”
Section: Membrane Bound Grasshopper Lazarillo Increases Lifespan Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that the p38a and p38b double-mutant flies are viable in nearsterile condition but hypersensitive to microbial infection (Chen et al, 2010). By contrast, p38c appears to be an atypical p38 MAPK, because it has mutations in the TGY motif, which is required for activating phosphorylation by MAP2Ks (Davis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…MAP3Ks phosphorylate and thereby activate MAP2Ks, and activated MAP2Ks in turn phosphorylate and activate MAPKs. In Drosophila, three p38-MAPK-encoding genes, p38a (also known as Mpk2), p38b and p38c, have been identified (Davis et al, 2008;Han et al, 1998a;Han et al, 1998b). As with mammalian p38s, Drosophila p38a and p38b have been shown to be activated by immune stimulation and various stressors, and flies lacking the p38a or p38b gene are susceptible to some environmental stressors (Craig et al, 2004;Cully et al, 2010;Han et al, 1998b).…”
Section: Introductionmentioning
confidence: 99%